FIBRILHAÇÃO AURICULAR: INCIDÊNCIA, PREVALÊNCIA E PERCENTAGEM DE HIPOCOAGULADOS NUMA CONSULTA HOSPITALAR DE UMA UNIDADE DE SAÚDE DO INTERIOR - de Carvalho Vilarinho, Maria Margarida (2022)
Introduction: Atrial fibrillation is the most frequent arrythmia in clinical practice, leading to an increase in the individual’s morbidity and overall mortality. This study aims to investigate the prevalence, incidence, percentage of individuals anticoagulated and the relationship between this arrythmia and other factors. Methods: Retrospective, descriptive and observational study in a sample of patients who attended Cardiology and Hypertension appointments in Centro Hospitalar Universitário Cova da Beira for six months in 2019, through the consultation of clinical processes at SClínico, from which data was collected such as gender, age, anticoagulant medication, presence or absence of atrial fibrillation, hypertension, obstructive sleep apnea, smoking habits, body mass index and events of stroke, transient ischemic attack and/or acute myocardial infarction. Statistical analysis was performed by using SPSS®. Results: In a sample of 391 people, there was a prevalence of 16,9% of atrial fibrillation and an incidence of 5,23 per 100 patients in 6 months. Of the patients with atrial fibrillation, 68,2% are anticoagulated, being Rivaroxaban the one that is the most used of all anticoagulants: 28,9%. Half of the patients with atrial fibrillation are males, 39,4% are between 70 and 79 years old, 87,9% have hypertension, 25,8% have obstructive sleep apnea, 6,1% are smokers, 4,5% had a stroke, 4,5% had a transient ischemic attack and 16,7% had an acute myocardial infarction. There was no relationship found between atrial fibrillation and the other variables, except for age and anticoagulation. Conclusion: The prevalence of atrial fibrillation obtained in this study is high, which entails that an early diagnosis is needed due to the morbidity and mortality that this arrythmia causes and that it is crucial to prevent the risk factors that lead to atrial fibrillation, reinforcing the role of Primary Health Care in them.